Future-Ready Economies: The Impact of Digitalization on Uzbekistan-South Korean Economic Relations (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article explores the impact of digitalization on the economic relations between Uzbekistan and South Korea, highlighting how both countries leverage technology to strengthen their economic futures. Uzbekistan is implementing significant digital reforms under its "Digital Uzbekistan 2030" initiative to enhance economic diversification and global integration. In contrast, South Korea, a global leader in digital innovation, uses its advanced technological infrastructure to expand its economic influence and maintain a competitive edge.By examining digital policies, joint ventures, and specific technological initiatives, the analysis reveals how digitalization is reshaping trade, industry, and bilateral cooperation between these nations. The study provides insights into the successes, challenges, and future opportunities for economic collaboration in the digital era, suggesting that digitalization is crucial for sustainable economic growth and international competitiveness.